Enriching my teaching around the inverse order relationship in unit fractions at the Grade 5 level through the inclusion of musical activities: an action research case study - Lovemore, Tarryn Shirley (Rhodes University, Faculty of Education, Department of Education, 2020)
This research study explored how the use of musical activities, specifically based on note values, might enrich my teaching around the inverse order relation of unit fractions in my Grade 5 mathematics classroom. Much research has identified fractions as a problematic concept to teach in primary schools. Curriculum expectations of mathematics and music, as well as prior research, recognise a link between these two subject areas. Based on these connections between mathematics and music, I make the case for further research into practical ways in which music and mathematics can be integrated to support teaching and learning in the South African context. This study is located within a qualitative and interpretive framework. The concepts of integration, learning style theory, Gardner's multiple intelligences and Bresler's styles of arts integration guide the research. I made use of practical and theoretical activities relating to note values in music. I explored these strategies and the use of learning support materials through an action research case study, in which I engaged in cycles of trialing, reflecting, adjusting and re-trialing within the 'case' of my own mathematics class. Data sources comprised of my reflective journal, learner feedback, video- and audio-recorded lessons, examples of learners' work and interviews with critical peers who observed critical moments from the video recordings. I was guided through the analysis phase by two analytical frameworks: Karsenty and Arcavi's Six Lense Framework (SLF) and Adler and Ronda's Mathematics Discourse in Instruction (MDI) framework which I adapted. Using three key lessons, I provide detailed descriptions of how the lessons progressed and then identify and discuss some of the key findings and recurring themes in relation to my study's research question and goals. Through this process, I show that my integration of mathematics and musical activities helped promote active engagement amongst learners and provided them with co-equivalent opportunities to appreciate the importance of note values in music, and relate this back to understandings around the inverse order relation of unit fractions.
Keywords: Mathematics -- Study and teaching (Elementary) -- South Africa -- Case studies; Interdisciplinary approach in education -- South Africa -- Case studies; Music -- Study and teaching (Elementary) -- South Africa -- Case studies; Music -- Mathematics; Musical notation -- Study and teaching (Elementary)